La importancia de aplicar las técnicas grafoplásticas para el desarrollo de la motricidad fina de los niños y niñas de educación inicial nivel II de la unidad educativa fiscal Camino del Inca de la ciudad de Quito, parroquia Turubamba en el periodo 2013-2014 - Medina Pineda, Mayra Fabiola (2014)
This research aims to study "THE IMPORTANCE OF TECHNICAL GRAFOPLÁSTICAS APPLY FOR THE DEVELOPMENT OF FINE MOTOR SKILLS OF CHILDREN OF EARLY CHILDHOOD EDUCATION LEVEL OF EDUCATION UNIT II FINANCIAL INCA TRAIL OF QUITO, PARISH TURUBAMBA IN THE PERIOD 2013-2014" same as developed for the degree of BA in Child Psychology and Early Childhood Education, meeting the standards established for graduation at the National University of Loja. To determine the present investigation the general objective idea was to establish the importance of the application of techniques in plastic Graph Fine Motor development in children Education Level II Initial Fiscal Inca Trail in Education Unit the period 2013-2014. The methods that were used in the preparation of this research work were; Scientific, Deductive, Inductive, Analytical - Synthetic and Statistical Model that allowed for discussion and comparison of the proposed variables. Two instruments were applied; Survey teachers and Test Dexterimetro of Goodard, aimed at children Initial Education Level 2 of the Inca Trail Attorney of the City of Quito Education Unit to measure fine motor skills of children acquired. The data analysis was the performed using information obtained by surveys and test through tables and graphs them were analyzed and interpreted, respectively, and these results will come to the conclusions and recommendations, which helped to improve and understand the activities learning with children from 4-5 years.